INCOME DISTRIBUTION AND ZAKAT CONTRIBUTION IN MALAYSIA - Nur Afiqah Mohd Fizol; Nur Syahirah Syahirin; Nurul Suhada Sarnubi; Safinatun Najah Seman; Nurul Kauthsar Razman; Fuadah Johari (IQTISHADUNA, 2022)
One of the fundamental obligations of every Muslim is to pay Zakat. The asnaf group may receive assistance from Zakat payments and income distribution to survive financial difficulties. This article aims to describe how Malaysian Zakat income and distribution function. The significance of Zakat donations to the community for its economic development is discussed in the first paragraph of this article. The history of the Zakat contribution controversy and Sharia-based theory are then covered. The study's conclusion indicates an imbalance in the distribution of Zakat by the state in Malaysia based on the country's poverty rate. In order to ensure that Zakat's contribution to the community is effective, the article underlines the necessity for a thorough action plan to ensure that no Muslim group is overlooked or marginalised. To fulfil their different obligations and more effectively and efficiently meet the responsibility to donate Zakat, every Muslim community member must honestly collaborate and adhere to the detailed action plan.